Akuntabilitas Direksi dan Dewan Komisaris atas Misstatement Prospektus IPO: Standar Due Diligence, Tanggung Renteng, serta Sanksi Pidana–Administratif dalam UU P2SK : Penelitian - Rian Mangapul Sirait; Anra Yoparisa Nasution; Iqbal Doly Indra Utama (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Abstract The capital market relies on integrity and transparency of information. In the Initial Public Offering (IPO) process, the prospectus is the central document containing material facts as the basis for investment decisions. However, the complexity of the information contained in the prospectus opens up the risk of misstatements or omissions that can harm investors. The Board of Directors and the Board of Commissioners, as the company's management and supervisory organs, bear legal responsibility to ensure the accuracy and completeness of information through due diligence mechanisms as a standard of prudence (duty of care) and a manifestation of fiduciary duty. This article examines the construction of the Directors' and Commissioners' liability for prospectus misstatements under the Capital Market Law (UUPM) and the Limited Liability Law (UUPT), including civil liability, particularly joint and several liability under Article 80 of the UUPM, the scope for defense through due diligence defense and the relevance of the business judgment rule, as well as criminal and administrative consequences. Strengthening regulations through Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (UU P2SK) emphasizes the enforcement dimension, including increased sanctions and the strengthening of the Financial Services Authority (OJK)'s role in mitigating IPO risks.